Pengembangan Wawasan Manajerial, Pendampingan UMKM “Rumah Makan Padang Sari Bundo” - Puja Sagita; Siska Yulia; Wiliam Janaldo; Sudarmiatin Sudarmiatin; Yuli Soesetio (FKIP, Universitas Palangka Raya, 2026)
The rapid development of digital technology and changes in consumer behavior require Micro, Small, and Medium Enterprises (MSMEs) to adapt in marketing and service aspects. Rumah Makan Padang Sari Bundo, a culinary MSME located in Pasir Gadung, Cikupa, faced several problems, including limited use of social media, underutilization of digital platforms such as Google Maps, and the absence of cashless payment systems. This community service activity aimed to improve business competitiveness through the digitalization of marketing and services. The method applied was the PDCA (Plan-Do-Check-Act) approach, consisting of planning, implementation, evaluation, and follow-up stages. The implementation included creating Instagram and WhatsApp Business accounts, optimizing Google Maps, and applying the QRIS digital payment system. The results showed increased business visibility, easier customer access to information, and improved transaction convenience through cashless payments. Furthermore, digitalization enabled the MSME to become more adaptive to technological developments and modern consumer needs. Therefore, digital transformation at Rumah Makan Padang Sari Bundo represents an important step in supporting business sustainability and improving competitiveness in the digital era.